The agricultural dilemma: how not to feed the world - Stone, Glenn Davis (London Routledge, 2022)
This book is about the three fundamental forms of agriculture: Malthusian (expansion), industrialization (external-input-dependent), and intensification (labor-based). The best way to understand the three agricultures, and how we tend to get it wrong, is to consider what drives their growth.